Retro-innovation and Corporate Social Responsibility (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
The paper deals with the retro-innovation and their importance to corporate social responsibility (CSR). Corporate social responsibility is a process with the aim to encourage a positive impact through activities on the environment, consumers, employees, communities, and all other stakeholders of the public sphere. The accelerated rate of technological and social change influences on the society. The main social problems are symptoms of future shock. Retro-innovation trend is emerging against an accelerating backdrop of "datafication". New products are designed to connect customers with the past in ways that are nostalgic, interactive and environmental. CSR thanks to the retroinnovation encourages has a positive impact on the all stakeholders and eliminates the future shock.